Effects of sildenafil citrate on defibrillation efficacy - Krekwit Shinlapawittayatorn (2018)
Introduction: Although fatal arrhythmia and sudden death have been reported in patients taking sildenafil citrate, its effect on defibrillation efficacy has not been investigated. The aim of this study was to test the hypothesis that sildenafil citrate increases the shock strength required to successfully defibrillate during ventricular fibrillation (VF). Methods and Results: A total of 26 pigs (20-25 kg) were randomly assigned into three groups. In each group, the defibrillation threshold (DFT) was determined at the beginning of the study using a three-reversal up/down protocol. Each shock (RV-SVC, biphasic) was delivered after 10 seconds of VF. Group 1 (n = 10) received 50 mg and group 2 (n = 10) received 100 mg of sildenafil citrate intravenously at a rate of 2 mL/minute for 50 minutes. Group 3 (n = 6) received 100 mL of saline intravenously at the same rate as in group 1. The DFT was determined again after the drug (drug-DFT) and saline (saline-DFT) administration. For 100-mg sildenafil citrate infusion, the DFT (483 ± 39 V, 18 ± 3 J) was significantly (P < 0.003 and P < 0.01, respectively) higher than the control-DFT (407 ± 123 V, 13 ± 7 J). This sildenafil citrate infusion increased the DFT ∼19% by voltage, and ∼38% by total energy. After 50-mg sildenafil citrate infusion, the DFT (454 ± 28 V, 15 ± 2 J) was not different than the control DFT (449 ± 28 V, 15 ± 2 J). Saline infusion (391 ± 18 V, 12 ± 1 J) did not alter the control DFT (399 ± 22 V, 12 ± 1 J). Conclusion: The 100-mg sildenafil citrate infusion, representing a supra-therapeutic plasma level, significantly increased the DFT. This finding indicates that VF occurring during supra-therapeutic sildenafil citrate treatment would require a stronger shock to successfully defibrillate.